Students’ perceptions of emergency remote teaching in a writing course during COVID-19 - Guskaroska, Agata; Dux Speltz, Emily; Zawadzki, Zoë; Kurt, Şebnem (Frontiers in Education, 2022)
The COVID-19 pandemic forced most of the educational institutions in the USA to quickly transfer to emergency remote teaching, finding many instructors and students unprepared. This study explored university students’ perspectives in a composition course during the emergency period and proposes guidance on how to design a ‘student-friendly’ online learning environment. This study examines the students' concerns about and challenges with emergency remote teaching, the course’s benefits during the remote teaching period, and students’ recommendations for improvement. The research was conducted in seven sections of a multimodal composition course at a large, Midwestern university. Participants responded to a virtual discussion board at the beginning of online instruction and to a survey at the conclusion of online instruction to provide this information. Qualitative analysis of responses—guided by the Community of Inquiry (CoI) framework—showed that the participants expressed challenges with staying motivated, completing coursework, and feeling a social disconnect from instructors and classmates. Benefits expressed by the participants included increased flexibility in their schedules, improved time management skills, and increased virtual communication with instructors. This study highlights suggestions that can be used to guide the design of composition courses and pedagogical practices during situations of emergency in the future.